2015
DOI: 10.1111/ijcs.12231
|View full text |Cite
|
Sign up to set email alerts
|

How does the theory of consumption values contribute to place identity and sustainable consumption?

Abstract: The importance of consumers’ role in sustainable consumption is reflected in the vision of the Sustainable Development Education Panel: To educate consumers to make informed consumption decisions, to take responsibility for their actions and to realize the impact of consumption decisions on future generations. However, educating and informing consumers alone is unlikely to change deeply entrenched unsustainable consumption behaviour. A multi‐faceted approach is required – enforcing sustainable development init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 63 publications
3
52
1
2
Order By: Relevance
“…Specifically, Hur, Yoo, and Chung (2012) revealed that functional value, epistemic value, and emotional value drive purchase intention among South Korean urban consumers. Lee et al (2015) found that place identity, which drives environmental attitudes and sustainable consumption behaviour, was significantly influenced by functional, social, emotional, epistemic, and conditional value. A study conducted in Malaysia among green product consumers revealed that social and epistemic values drive environmental concerns (Mohd Suki & Mohd Suki, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Hur, Yoo, and Chung (2012) revealed that functional value, epistemic value, and emotional value drive purchase intention among South Korean urban consumers. Lee et al (2015) found that place identity, which drives environmental attitudes and sustainable consumption behaviour, was significantly influenced by functional, social, emotional, epistemic, and conditional value. A study conducted in Malaysia among green product consumers revealed that social and epistemic values drive environmental concerns (Mohd Suki & Mohd Suki, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted in Malaysia, consumption values were considered as predictors for the desire among consumers for green products (Mohd Suki & Mohd Suki, 2015). Other scholars asserted that consumption values are the motivational drivers for suburban choices in New Zealand (Lee, Levy, Yap, & Sheau, 2015). Researchers have also noted that most consumption values are independent, and changes in one dimension may not necessarily result in changes in others.…”
Section: The Consumption Value Modelmentioning
confidence: 99%
“…Some scholars have directly added variables, such as green product information, environmental performance and confidence, price sensitivity, individual environmental literature, and external motivating factors, into VAB to study their direct impact on green purchase behavior [ 6 , 30 , 45 ]. Intermediary or moderating variables, such as green product quality and place identity, were also added into the VAB framework, which revised the original path of VAB [ 6 , 48 ]. The development of the VAB model has not only improved the explanatory power and applicability of the model, but it has also facilitated a deeper level of examination on the research problems.…”
Section: Discussionmentioning
confidence: 99%
“…Social affiliation motivates the consumer to behave in the same way that of their social class (Candan and Yildirim 2013). Consumers like to consume those brands that represent their social status (Lee et al 2015). Consumers think their green purchase behavior is a modern way of life, and they like to consume it for their social identity in society (Kumar and Ghodeswar 2015).…”
Section: Social Valuementioning
confidence: 99%